2014
DOI: 10.1007/s11356-014-2903-y
|View full text |Cite
|
Sign up to set email alerts
|

Filter materials for metal removal from mine drainage—a review

Abstract: A large number of filter materials, organic and inorganic, for removal of heavy metals in mine drainage have been reviewed. Bark, chitin, chitosan, commercial ion exchangers, dairy manure compost, lignite, peat, rice husks, vegetal compost, and yeast are examples of organic materials, while bio-carbons, calcareous shale, dolomite, fly ash, limestone, olivine, steel slag materials and zeolites are examples of inorganic materials. The majority of these filter materials have been investigated in laboratory studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Organic filter material such as lignite [47] and rice husk [48] were used successfully in the removal of metal and sulfate from mine drainage. According to [4], there are some disadvantages in using filter material in large scale, namely: high cost, variable composition of mine water, instability, and risk of leaching hazard substances from filter material.…”
Section: Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic filter material such as lignite [47] and rice husk [48] were used successfully in the removal of metal and sulfate from mine drainage. According to [4], there are some disadvantages in using filter material in large scale, namely: high cost, variable composition of mine water, instability, and risk of leaching hazard substances from filter material.…”
Section: Filtrationmentioning
confidence: 99%
“…cassava peel) is very effective in removing metals at low concentration compared to conventional methods at large scale [2]. Developing countries cannot afford much budget to protect their local environment and bioremediation [3], adsorption [2] and filtration [4] seem to be economical strategies that, if applied properly, can be viable solutions for mine water treatment in, for instance, Moatize (Mozambique).…”
Section: Introductionmentioning
confidence: 99%
“…The presentation above has already shown that O2 scavengers including SSF should precede Fe 0 /sand filters. The situation of multiple contaminant mixtures which may not be efficiently treated by a single technology [189] is an opportunity to compare Fe 0 filtration to other available affordable filtration systems [190] and shape multi-barrier systems involving Fe 0 filters. Contaminants possess different properties with respect to adsorptive behavior, degradation potential, molecular size, solubility, and surface charge [191].…”
Section: Comparing Fe 0 Filters To Other Technologiesmentioning
confidence: 99%
“…Because multiple contaminant mixtures may contain positively charged species as well, it is important to comparatively test Fe 0 and other materials under the same operational conditions. Relevant filter materials include activated carbons, bark, bio-carbons (biochar), wood charcoal, calcareous shale, chitin, chitosan, commercial ion exchangers, dairy manure compost, dolomite, fly ash, lignite, limestone, olivine, peat, rice husks, steel slag materials, vegetal compost, yeast, and zeolites [190,192].…”
Section: Comparing Fe 0 Filters To Other Technologiesmentioning
confidence: 99%
“…Before 2007, all waste was dumped in the landfills, which were not equipped with leachate or gas collection systems. Therefore, leachate and gas found their way into the surrounding environment [8][9][10][11][12]. The use of as many recycling materials as possible is an important point.…”
Section: Introductionmentioning
confidence: 99%